2019
DOI: 10.1136/flgastro-2018-101057
|View full text |Cite|
|
Sign up to set email alerts
|

Antibiotics and probiotics in inflammatory bowel disease: when to use them?

Abstract: Antibiotics and probiotics are often used as adjunctive therapy in inflammatory bowel disease. However, data are limited and randomised controlled trials are too inconsistent to provide generalised recommendations for their use in all patients with ulcerative colitis or Crohn’s disease. Antibiotics are best used in the management of infectious complications and fistulas in Crohn’s disease and, perhaps, in reducing the intensity of inflammation in luminal disease. Ciprofloxacin, metronidazole and rifaximin have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 96 publications
0
23
0
2
Order By: Relevance
“… Increased in abundance [ 128 ]. Increased intestinal permeability and lipopolysaccharide release through metabolism of bile-acids to oxo-bile [ 144 , 145 ] Escherichia spp ., Dorea spp. Increased in abundance [ 131 , 135 , 136 ] Coprococcus spp., Eubacterium spp., Faecalibacterium spp., Prevotella spp.…”
Section: What Is Currently Known On the Topicmentioning
confidence: 99%
See 1 more Smart Citation
“… Increased in abundance [ 128 ]. Increased intestinal permeability and lipopolysaccharide release through metabolism of bile-acids to oxo-bile [ 144 , 145 ] Escherichia spp ., Dorea spp. Increased in abundance [ 131 , 135 , 136 ] Coprococcus spp., Eubacterium spp., Faecalibacterium spp., Prevotella spp.…”
Section: What Is Currently Known On the Topicmentioning
confidence: 99%
“…Findings from recent work showed that the ability of an introduced microbe to successfully colonize the gut depends on the structure of the resident gut microbiota [ 144 ], a factor that has so far been overlooked in microbial intervention-based clinical trials and that might explain discrepancies in animal models and human trials. Nonetheless, intervention with a multispecies consortium of bacteria has shown to be effective in the maintenance of remission in patients with UC but not in those with CD [ 145 ]. Meta-analysis of intervention trials in which various combinations of bacterial strains were administered to adults with T2DM showed moderate improvements in hyperglycemia [ 146 ].…”
Section: What Is Currently Known On the Topicmentioning
confidence: 99%
“…Results from large scale clinical trials and meta-analyses have been mixed with some analyses finding mild to moderate benefits in disease activity scores (65,66) and others finding no benefit (67). Furthermore, probiotics and fecal microbiota transplant (in UC patients) may induce or maintain remission in some IBD patients (68)(69)(70).…”
Section: Observations In Human Ibdmentioning
confidence: 99%
“…It has been experimentally used in rats, and the results of its administration were encouraging [9,10], although, again, there is a lack of controlled clinical studies. Finally, probiotics of a special type and dosage could in fact reduce the inflammatory process in patients with active ulcerative colitis UC [11][12][13].…”
Section: Introductionmentioning
confidence: 99%